MODERATED IDENTITY POLITICS: MUSLIM VOTERS AND RELIGIOUS DEPOLARIZATION IN NORTH MALUKU’S 2024 GUBERNATORIAL ELECTION - Deni, Aji; Wance, Marno; Muhtar, Muhtar (Universitas Padjadjaran, 2025)
This study examines religious polarization in North Maluku, proposing moderated identity politics and a hybrid representation model to explain post-conflict electoral behavior. It highlights local leaders who strategically balance identity appeals with cross-group alliances, integrating structural and agential factors to advance electoral theory and offer a replicable model for mitigating identity-based conflict in plural Indonesian regions. Using a mixed-methods sequential explanatory design, quantitative data were first collected from 100 proportionally sampled respondents. Subsequently, in-depth qualitative interviews were conducted with 17 key informants. Data triangulation, comparing survey results with interview findings, ensured consistency and strengthened the validity of the research conclusions. The study presents four novel contribution findings. First, it challenges conventional religious voting, demonstrating Sherly Tjoanda’s Catholic victory in a Muslim-majority province, attributed to economic pragmatism, political legacy, and networks over religious affiliation. Second, it introduces the Hybrid Representation Model, combining development performance with a moderate religious figure. Third, it refines voter decision-making through Post-Conflict Electoral Rationality and welfare populism, illustrating how trauma fosters pragmatism. Finally, it develops Moderated Identity Politics, integrating local factors like Nahdlatul Ulama’s influence and conflict trauma to reduce polarization and promote electoral pragmatism. The 2024 North Maluku gubernatorial election, with the Sherly-Sarbin ticket’s victory, exemplified pragmatic considerations outweighing religious identity. This model outcome establishes Moderated Identity Politics that can depolarize elections by endorsing competence-based, cross-faith alliances, and prioritizes a competence-plus-credibility approach. In contexts with a dominant, moderate Islamic organization and where economic competition is not a zero-sum game.